STUDI KORELASI ANTARA MOTIVASI BERPRESTASI DENGAN DISIPLIN BELAJAR SISWA DI SMAN 2 SANGATTA UTARA - Poppy Putri Kusumaning Ayu (Al-Rabwah, 2021)
The purpose of this study was to determine how much the correlation between achievement motivation and learning discipline of class XI students at SMA Negeri 2 Sangatta North. The hypothesis of this research is that there is a significant correlation between achievement motivation and the learning discipline of class XI students at SMA Negeri 2 Sangatta North. This study uses data collection techniques that complement each other, namely the questionnaire technique to obtain research data by scoring from 135 respondents which are then processed using the Product of the Moment Correlation formula, an observation technique to directly observe the activities of class XI students of SMA Negeri 2 Sangatta North, and documentation techniques to get some supporting data. To answer the problem formulation, how big is the correlation between achievement motivation and learning discipline, knowing the r_xy value is 0,404 which is greater than the r_table value of 0,169 with an interpretation value of 0,40 – 0,599 which means there is a correlation between achievement motivation and student learning discipline, but by looking The correlation interpretation table is moderate. And to answer the hypothesis in the study, knowing the t_count value is 5,093 which is greater than the t_table value 1,978 with a significance level of 5% or 0,05 means that H_a is accepted so that the variable X (achievement motivation) has a significant correlation with the variable Y (discipline student learning).